Spirituality, Religiosity, and Weight Management among African American Adolescent Males: The Jackson Heart KIDS Pilot Study - Bruce, Marino A. (Behav Med, 2016)
Spirituality and religion have been identified as important determinants of health for adults; however, the impact of faith-oriented factors on health behaviors and outcomes among African American adolescent males has not been well studied. The purpose of this study is to examine the relationship between religiosity and spirituality and obesity-related behaviors among 12–19 year old African American males (N=105) in the Jackson Heart Kids Pilot Study. Key variables of interest are church attendance, prayer, daily spirituality, weight status, attempts to lose weight, nutrition, physical activity, and stress. Daily spirituality is associated with whether or not an individual attempts to lose weight. The results from logistic regression models suggest that daily spirituality increases the odds that African American male adolescents attempt to lose weight (OR=1.22, CI: 1.07–1.41) and have a history of diet-focused weight management (OR=1.13, CI: 1.02–1.26). Future studies are needed to further explore the association between religion, spirituality and obesity-related behaviors.